PENGARUH PENGGUNAAN MEDIA SOSIAL TIKTOK TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI MI ISLAMIYAH PERGURUAN PALEMBANG - Rizky Oktariyani; Middya Boty; Siti Fatimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the use of tiktok social media on the learning achievement of students in grade V in the Indonesian Language subject at MI Islamiyah Perguruan Palembang. This study uses a quantitative approach. The type of research used is pre-experimental designs with a one group pretest-posttest pre-experimental design. The sample in this study was 24 grade V students. The data validity technique uses validity and reliability tests. The data analysis technique uses normality tests and hypothesis tests. The results of the pre-test data that have not used tiktok social media as a learning medium obtained an average of 37.50. While the post-test data after implementing tiktok social media as a learning medium obtained an average of 82.92, it can be seen that student learning achievement is higher after implementing tiktok social media than the learning achievement of students who have not implemented tiktok social media. The results of the research and data analysis were obtained using the paired sample t-test with the help of SPSS for windows version 25 with a significant value of 5%, namely 0.000 <0.05. Because the significant value is less than 0.05, H0 is rejected and Ha is accepted. This shows that there is a significant influence of tiktok social media on student learning achievement in the Indonesian language subject of class V MI Islamiyah Perguruan Palembang.